THE INFLUENCE OF CONSUMPTION VALUES AND ATTITUDE ON FRUIT PURCHASE INTENTION: A CONCEPTUAL ANALYSIS - Fasyni, Awisal; Muthusamy, Geetha; Wahid, Siti Daleela Mohd; Mohamad, Wan Normila (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Enhancing fruit consumption seeks to elevate the fruit industry while tackling elevated incidences of non-communicable diseases (NCDs) and obesity. This research aims to establish a framework derived from a literature review to elucidate the elements affecting customer propensity to purchase fruits. A comprehensive literature review on the intention to purchase fruits was conducted to establish a conceptual framework that delineates the relationship between consumption values, attitudes, and fruit purchasing intentions. The research demonstrates that possessing positive consumption values may foster a favorable attitude that results in customers’ inclination to purchase fruit. The conceptual model will aid practitioners in understanding the influence of consumer consumption values and attitudes on boosting purchasing intentions. Future study should include quantitative and structural equation modeling (SEM) to validate the effects of the proposed framework and hypotheses.